Digital Marketing Management Through Community-Based Training: A Case Study Of “Go Digital UMKM” Program In Surabaya - Syamsul Arifin; Agus Sanjaya (International Journal of Economics, Science, and Education, 2025)
Digital marketing is essential for MSMEs in the post-pandemic era, yet many lack the skills to leverage online platforms effectively. This study investigates the impact of the “Go Digital UMKM” program, a collaborative community-based training organized by Universitas Surabaya and the Surabaya City Cooperative Agency, held in April 2025. The training focused on basic digital branding, social media optimization, and online selling. Using a qualitative case study approach, data were collected through observations, interviews, documentation, and pre-/post-tests. Findings show that participants experienced an average 42% improvement in digital marketing knowledge, with increased confidence in using Instagram and Shopee. The program highlights the effectiveness of contextual, hands-on training in improving MSME digital capability and suggests a replicable model for other regions.